Taxonomic expansion and reorganization of Flaviviridae - Simmonds, Peter; Butković, Anamarija; Grove, Joe; Mayne, Richard; Mifsud, Jonathon C O; Beer, Martin; Bukh, Jens; Drexler, J Felix; Kapoor, Amit; Lohmann, Volker; Smith, Donald B; Stapleton, Jack T; et al. (Nature microbiology, 2025)
Flaviviridae is a family of non-segmented positive-sense RNA viruses that includes major pathogens such as hepatitis C virus, dengue viruses and yellow fever virus. Recent large-scale metagenomic surveys have identified many RNA viruses related to members of this family, such as orthoflaviviruses and pestiviruses. These viruses diverge by having different genome lengths and configurations, and host range. Here we performed an analysis of RNA-directed RNA polymerase (RdRP) hallmark gene sequences of flaviviruses and 'flavi-like' viruses. We uncovered four divergent clades and multiple lineages that are congruent with phylogenies of their helicase genes, protein profile hidden Markov model profiles, and evolutionary relationships based on predicted RdRP protein structures. These results support their classification into three families (Flaviviridae, Pestiviridae and Hepaciviridae) and 12 genera in the established order Amarillovirales, with groupings correlating with genome properties and host range. This taxonomy provides a framework for future evolutionary studies on this important viral family.